Fast Analytical Method for Authentication of Chili Powder from Synthetic Dyes Using UV-Vis Spectroscopy in Combination with Chemometrics - Eti Rohaeti; Khoirotul Muzayanah; Dewi Anggraeni Septaningsih; Mohamad Rafi (Universitas Gadjah Mada, 2019)
Chili is widely used in many food products, especially in Indonesia food. Sometimes a synthetic dye, i.e., rhodamine B or red textile dye were found in commercial chili powder. A fast, precise and accurate analytical method is necessary to authenticate chili powders from the two synthetics dye as they can cause a health problem. A combination of UV-Vis spectroscopy and chemometrics (multivariate analysis) were used in this study to detect rhodamine B and red textile dye present in chili powder samples. Authentication of chili powder from the two dyes by principal component analysis (PCA) with absorbance data from the UV-Vis spectra of samples was not able to classify all of the samples into each group (pure and adulterated chili powder). Fortunately, by using principal component analysis-discriminant analysis (PCA-DA), approximately 89 and 86% of chili samples mixed with rhodamine B and commercial red textile dye were successfully classified into their corresponding group respectively. The combination of UV-Vis spectroscopy with PCA-DA could be used for fast authentication of chili powder from rhodamine B and textile dye used in this study.